Cloud Manufacturing: Tinjauan Literatur dan Pengembangan Layanannya untuk Perencanaan Fasilitas Produksi - Agus Sutanto (Jurnal Optimasi Sistem Industri, 2014)
Cloud Manufacturing is an advanced manufacturing model which provides services by utilizing a shared resource pool such as computers, servers, networking, Internet and application softwares. The term Cloud Manufacturing in the engineering literature is still fairly new. it comes from the term Cloud Computing which is earlier known as Internet services on demand. Here includes Software as a Service (SaaS) along with infrastructure, platform and other delieveries as a service. First introduced by F. Tao in 2011, Cloud Manufacturing combines the latest technologies such as cloud computing, internet of thing, manufacturing object virtualizations and service-oriented computing services. The advanced manufacturing service models related to this terminology will be described as literatur reviews in this paper. At the end of this paper was given a case study of the application of the Cloud Manufacturing for designing a web-based production facilities layout as a cloud software as a service for the users.